Hydrolysis of synthetic polyesters by Clostridium botulinum esterases. Issue 5 (20th November 2015) - Perz, Veronika; Baumschlager, Armin; Bleymaier, Klaus; Zitzenbacher, Sabine; Hromic, Altijana; Steinkellner, Georg; Pairitsch, Andris; Łyskowski, Andrzej; Gruber, Karl; Sinkel, Carsten; Küper, Ulf; Ribitsch, Doris; et al.
ABSTRACT: Two novel esterases from the anaerobe Clostridium botulinum ATCC 3502 (Cbotu_EstA and Cbotu_EstB) were expressed in Escherichia coli BL21‐Gold(DE3) and were found to hydrolyze the polyester poly(butylene adipate‐co‐butylene terephthalate) (PBAT). The active site residues (triad Ser, Asp, His) are present in both enzymes at the same location only with some amino acid variations near the active site at the surrounding of aspartate. Yet, Cbotu_EstA showed higher k cat values on para ‐nitrophenyl butyrate and para ‐nitrophenyl acetate and was considerably more active (sixfold) on PBAT. The entrance to the active site of the modeled Cbotu_EstB appears more narrowed compared to the crystal structure of Cbotu_EstA and the N‐terminus is shorter which could explain its lower activity on PBAT. The Cbotu_EstA crystal structure consists of two regions that may act as movable cap domains and a zinc metal binding site. Biotechnol. Bioeng. 2016;113: 1024–1034. © 2015 Wiley Periodicals, Inc. Abstract : Crystal structure of the novel anaerobic polyesterase Cbotu_EstA (PDB: 5AH1) and schematic representation of the enzyme adsorbing to the polyester surface: Perz and coworkers have identified a new esterase from Clostridium botulinum with ability to hydrolyze the synthetic polyester PBAT (poly(butylene adipate‐co‐butylene terephthalate). During enzymatic hydrolysis of PBAT, water‐soluble hydrolysis products are released and can be quantified to determine the degree of polyester degradation. Moreover, analysis of the enzyme‐crystal structure provides an indication on the enzyme–polymer interaction.